Energy-efficient design, consumer awareness, and public policy - Carmen Arguedas; Sandra Rousseau (SERIEs - Journal of the Spanish Economic Association, 2021)
To facilitate the energy transition, regulators can choose between several policy options to stimulate energy-efficient design by firms. One possibility is to target firms directly through standards or subsidies. Alternatively, it is possible to influence firms indirectly by targeting firms' stakeholders and raising consumer awareness through information campaigns and education. In this paper, we focus specifically on the pivotal role of consumers and we investigate the effectiveness of subsidies, product standards, and education in improving firms' environmental performance through energy-efficient product design. In particular, we investigate the importance of the interaction effect between the regulation and consumers' environmental awareness under different market structures. We find that a policy based on a product standard can counteract the negative effects of crowding-out consumers' intrinsic motivation in a monopoly setting, although this counteracting effect is less powerful under a duopoly. However, a subsidy does not provide such a backup system and the full effect of crowding-out will be visible.
Keywords: C72; D43; H23; L51; Q58; 330; Environmental policy instruments; Energy-efficient design; Crowding-in/crowding-out; Consumer awareness